Behavior Based Automated Test Case Generation - Verma, Rohin (My University, 2010)
Test case generation is the most important part of the testing process. Most of the software fails because the test cases written are not able to detect errors. Generally testing is performed on requirements or the code, while the design is seldom concerned but in present work design based test case generation is proposed. Present work uses petal files, also called mdl files of Class diagram, Sequence diagram & State chart diagram to generate test cases. Class diagram can give information of static view of system. Sequence diagram can give information of time ordering of messages. Statechart diagram can give information of different states of system. Tool reads petal files of Class diagram, Sequence diagram & State chart diagram one by one and creates text files. Text files contain information extracted from Class diagram, Sequence diagram & State chart diagram. Then tables are created in database and using SQL *Loader all data from text files are entered into database. Finally using Netbeans IDE SQL queries are written in java to generate test cases from the data stored in database. In present work design is used for test case generation. Using design for test case generation helps to plan test cases early. Due to this most of the errors can be stopped and eliminated before going to next phase. This also leads to reduction of the effort required to remove errors at later stages. Generating test cases automatically from design is more realistic as compared to requirements or any other artifacts. Design based test cases cover both static as well as dynamic aspect of the system.
Keywords: Software Testing, UML Diagrams, Test Cases